Analysis Of Discipline And Work Environment On The Work Productivity Of Employees At The Auto2000 Workshop In Medan-Binjai - Muhammad Arkan Sitepu; Samrin Samrin; Abdi Setiawan (Universitas Dehasen Bengkulu, 2026)
The purpose of this study to analyse the effect of work discipline and work environment on the work productivity of employees at the AUTO2000 Workshop in Medan–Binjai. This study uses a quantitative approach with an associative research design. The population and sample of this study are all 35 employees of the AUTO2000 Workshop in Medan–Binjai, using a saturated sampling technique. Data were collected through questionnaires using a Likert scale and analysed using multiple linear regression with the SPSS program. The results showed that, partially, work discipline did not have a significant effect on employee productivity, while the work environment had a positive and significant effect on productivity. Simultaneously, work discipline and work environment have a significant effect on employee productivity. The results of this study are eXpected to be taken into consideration by management in improving productivity through the creation of a more conducive work environment.